Atomistic investigations of κ-carbide precipitation in austenitic Fe-Mn-Al-C lightweight steels and the effect of Mo addition. (15th January 2017) - Moon, Joonoh; Park, Seong-Jun; Jang, Jae Hoon; Lee, Tae-Ho; Lee, Chang-Hoon; Hong, Hyun-Uk; Suh, Dong-Woo; Kim, Seong Hoon; Han, Heung Nam; Lee, Bong Ho
Abstract: The effect of Mo addition on precipitation behavior of κ-(Fe, Mn)3 AlC during aging in austenitic Fe-Mn-Al-C lightweight steels was investigated. First-principles calculations indicate that substitution of Fe or Mn by Mo in κ-carbide is energetically unfavorable in the respect to formation energy, and it, moreover, increases strain energy contribution to interfacial energy between austenite matrix and κ-carbide. Atom probe tomography (APT) and transmission electron microscopy (TEM) analysis showed the results consistent with the calculations, i.e., Mo didn't partition into κ-carbide and delayed κ-carbide precipitation. Finally, nanoindentation experiments presented that Mo addition changed the aging hardening behavior, corresponding to κ-carbide precipitation behavior. Graphical abstract: